2017
DOI: 10.1016/j.jalz.2017.09.011
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for brain glucose dysregulation in Alzheimer's disease

Abstract: Impaired glucose metabolism due to reduced glycolytic flux may be intrinsic to AD pathogenesis. Abnormalities in brain glucose homeostasis may begin several years before the onset of clinical symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
275
2
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 386 publications
(297 citation statements)
references
References 45 publications
17
275
2
3
Order By: Relevance
“…Some studies demonstrate a relationship between insulin resistance and amyloid levels [49], whereas others do not [50]. In previous studies from our laboratory, we found no significant association between repeated measures of glucose intolerance, diabetes, or insulin resistance and either postmortem Aβ or in vivo PET-PiB [51], yet regions associated with amyloid and tau pathology show significantly higher tissue glucose concentrations in AD [52]. Thus, the exact relationship between these factors and amyloid accumulation demonstrated by PET imaging deserves further study.…”
Section: Discussionmentioning
confidence: 66%
“…Some studies demonstrate a relationship between insulin resistance and amyloid levels [49], whereas others do not [50]. In previous studies from our laboratory, we found no significant association between repeated measures of glucose intolerance, diabetes, or insulin resistance and either postmortem Aβ or in vivo PET-PiB [51], yet regions associated with amyloid and tau pathology show significantly higher tissue glucose concentrations in AD [52]. Thus, the exact relationship between these factors and amyloid accumulation demonstrated by PET imaging deserves further study.…”
Section: Discussionmentioning
confidence: 66%
“…PET imaging studies reveal impaired cerebral glucose utilization occurring very early in AD pathogenesis, even before overt clinical symptoms are evident (Friedland et al, 1989; Ceravolo et al, 2008). Findings from postmortem analyses reveal reductions in levels of glucose transporters and decrements in ETC complex activities and glycolytic flux in vulnerable brain regions of AD patients (Simpson et al, 1994; Valla et al, 2001; An et al, 2018). PD patients exhibit reduced glucose utilization in brain regions involved in motor control, and deep brain stimulation of the globus pallidus (which alleviates motor symptoms) increases glucose utilization in those brain regions (Fukuda et al, 2001).…”
Section: Perspective On How Mechanisms Of Aging Impact Neurological Dmentioning
confidence: 99%
“…In addition to the effect of S100B on RAGE-mediated ROS overproduction, this protein, at concentrations of ≥500 nM, enhances Aβ neurotoxicity. However, at lower concentrations, S100B showed a protective effect against the neurotoxicity of Aβ [25][26][27][28][29][30][31][32][33][34][35] [101]. Furthermore, recent studies suggested that elevated S100B levels have harmful effects on oligodendrogenesis and myelination through RAGE-dependent processes.…”
Section: S100 Protein Family As a Potential Biomarkers Of Admentioning
confidence: 99%
“…Cerebral regions sensitive to the aggregation of Aβ and NFTs display significantly higher glucose concentration in AD. Moreover, elevated levels of brain tissue glucose are associated with greater severity of both Aβ deposition and neurofibrillary pathology [35]. In a community-based controlled study performed together with pathological study of autopsy cases from this same community, authors have found that both T2DM as well as impaired fasting glucose were twice more prevalent in AD versus non-AD control subjects.…”
Section: Brain Energy Metabolism and Ad Onsetmentioning
confidence: 99%